Effect of Sputtering Power on Optical Properties of Nickel Oxide Electrochromic Thin Films - P. Panprom; P. Sritonwong; S. Limwichian; P. Eiamchai; V. Patthanasettakul; N. Nuntawong; M. Horprathum; C. Nawanil (My University, 2020)
The preparation and characterization of nickel oxide (NiO) thin film for electrochromic smart window applications are studied. The NiO thin film was prepared by the DC magnetron sputtering from a pure nickel target. The sputtering power was varies in the interval 50–200 W. The crystallinity and physical morphology of NiO films are characterized by X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM), respectively. The XRD result revealed that polycrystalline NiO thin films with preferred growth directions along (111) and (200) planes are obtained. Moreover, the electrochromic property of NiO thin films was investigated with a UV-Visible spectrophotometer. The colored state of the electrochromic cell was obtained by the ion insertion at the 1-V external applied bias in 0.1 M KOH. The reversibility between the colored and bleached states is confirmed by the optical transmittance. The result shows the optical contrast as high as 28.68.
Keywords: Non-blocking I/O; Nickel oxide; Electrochromic devices; Transition Metal Oxide Nanomaterials